Dyslexia Diagnostics Based on Eye Movements and Artificial Intelligence Methods: A Review - Gracheva, M.A.; Shalileh, S. (Klinicheskai͡a︡ i spet͡s︡ialʹnai͡a︡ psikhologii͡a, 2023)
The review considers methods of dyslexia diagnostics based on eye movement data and implemented on the basis of artificial intelligence. A number of studies have shown that eye movements in people with dyslexia may differ from those of people with normal reading abilities. Since 2015, studies have begun to appear in which the eye movements of observers with and without dyslexia were analyzed using various artificial intelligence methods. To date, there are a number of papers using both simple and more complex models (with neural networks and deep learning). This review discusses what accuracy of diagnosis has been achieved by researchers, for which groups of subjects and for which languages the current results have been shown, what types of algorithms have been used, and other practical aspects of conducting such diagnosis. According to the data analyzed, dyslexia diagnostics by eye movements and artificial intelligence methods is very promising and may have a significant impact on early diagnosing of reading problems. В обзоре рассмотрены методы диагностики дислексии по данным движений глаз, реализованные на основе искусственного интеллекта. В ряде работ было показано, что движения глаз у людей с дислексией могут отличаться от движений глаз у испытуемых того же возраста с нормальными способностями к чтению. Начиная с 2015 года в литературе стали появляться исследования, в которых анализ движений глаз нормотипичных испытуемых и испытуемых с дислексией осуществлялся с использованием различных методов искусственного интеллекта. На сегодняшний день существует ряд работ, использующих как простые модели, так и более сложные - с нейросетями и глубоким обучением. В обзоре обсуждается, какого качества диагностики удалось добиться исследователям, на каких группах испытуемых и для каких языков были показаны текущие результаты, какие типы алгоритмов использовались и другие практические аспекты проведения такой диагностики. Согласно проанализированным данным, диагностика дислексии с использованием движений глаз и методов искусственного интеллекта является очень перспективной и может оказать значительное влияние на раннюю диагностику нарушений чтения.